Analytical Review of Awareness About Rare Diseases Among Sharjah University Students - Alkarbi, Noura; Algharbawi, Fatima; Alnakhi, Wafa (Journal of Ecohumanism, 2025)
Individuals with rare disabilities face several challenges, such as isolation, stigma, discrimination, and fewer educational and employment opportunities. Few studies have examined individuals’ knowledge regarding rare disabilities in the Emirati context. This study aimed to identify the level of awareness about rare diseases among Emirati students. A total sample of 200 students was recruited as participants from the University of Sharjah self-administrative questionnaire was distributed to collect primary data and to examine the level of general knowledge of rare diseases to identify the extent of Emirati society’s awareness of these disabilities and the necessary therapeutic interventions. Our findings revealed that the participants had low awareness of rare diseases in the Emirati context. Furthermore, statistically significant differences were found between the level of awareness of rare diseases and students’ specialization. We recommend that more field visits to be conducted to expose the students at the university with the institutions that care for people with rare disabilities.. Raising awareness around rare diseases and disabilities will help in integrating individuals with rare diseases into society. Although our study findings contribute to the literature on rare diseases and disabilities in the Emirati context, it also has important implications for policymakers.